2020
DOI: 10.1088/1755-1315/537/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of nitrocellulose production from palm oil empty fruit bunches

Abstract: Nitrocellulose as a propellant can be obtained using a nitration reaction of Palm Oil Empty Fruit Bunches (POEFBs). In this study, we examined the sensitivity analysis of nitrocellulose production from POEFBs based on POEFBs price, electricity price, nitrocellulose price, and production capacity. The results showed that economic evaluations without sensitivity analysis deviations produced NPV, IRR, PBP and ROI in the values of US$ 1,437,097, 18.36%, 4.51 years and 16.31%. The most influential variable in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This could be due to all the kinetic models used in this study produce formic acid as a final product. The use of high temperature around 170 o C in the reactor will degrade furfural into resinification products where formic acid is the most dominant product [32][33][34][35][36]. In addition, a lot of lignin as a raw material component that was not hydrolyzed and humins as a by-product of the hydrolysis process were produced as byproduct according to Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to all the kinetic models used in this study produce formic acid as a final product. The use of high temperature around 170 o C in the reactor will degrade furfural into resinification products where formic acid is the most dominant product [32][33][34][35][36]. In addition, a lot of lignin as a raw material component that was not hydrolyzed and humins as a by-product of the hydrolysis process were produced as byproduct according to Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In which the samples were taken during the 10, 20, 30, 45, 90, and 120 minutes reaction at 150, 160, and 170 °C. From the experiment, it was found that the highest FA was formed at a reaction temperature of 170 °C after 20 minutes of reaction which produces 0.031 mol/L and 46.6 % mol of formic acid yield [29]. This method could also be implemented industrially in a reactor.…”
Section: Sustainable Formic Acid Extraction From Empty Fruit Bunch (Efb)mentioning
confidence: 96%